May Measurement Month 2018: an analysis of blood pressure screening in the Philippines. (28th August 2020) - Castillo, Rafael R; Mercado-Asis, Leilani B; Atilano, Alberto A; David-Ona, Deborah Ignacia; Diaz, Alejandro F; Granada, Carmela N; Bonzon, Dolores D; Vilela, Gilbert C; Chua, Carlos L; Gomez, Lynn A; Oliva, Raymond V; Morales, Dante D; et al.
Abstract: Building on the gains of May Measurement Month 2017 (MMM17), the Philippine Society of Hypertension once again took part in MMM18 to raise awareness of high blood pressure (BP) in the country and to harness opportunistic BP screening in detecting unaware hypertensive individuals and referring them for treatment. We followed the standard MMM18 protocol designed by the International Society of Hypertension, utilizing convenience sampling with volunteer investigators, taking three sitting BP measurements of volunteer adults (≥18 years). Basic data on demographic, lifestyle, and environmental factors were also taken. We analysed 177 176 screened individuals from the Philippines. Of these, 29.1% (51 527) had also participated in MMM17, whereas 68.8% (121 893) were new screenees; and 14.2% (25 232) had their BP taken for the first time ever. After multiple imputation, 39.0% (69 126) were hypertensive. Of these, 50.3% (34 795) were aware they were hypertensive. 49.9% (34 491) were on antihypertensive medication, 58.0% (20 010) of whom had controlled BP <140/90 mmHg. Only 28.9% of all participants with hypertension had controlled BP. Systolic BPs and diastolic BPs were significantly higher in the overweight and obese, in those receiving antihypertensive medications, in patients with diabetes, and significantly lower in pregnant women. MMM18 has again shown that opportunistic BP screening, harnessing volunteers, is a pragmatic public health measure to improve awareness and treatment rates of raised BP.